American as paneer pie - Kelkar, Supriya, 1980- (Simon & Schuster Books for Young Readers, 2021)
When a racist incident rocks her small Michigan town, eleven-year-old Lekha must decide whether to speak up or stay silent, even as she struggles to navigate her life at home, where she can be herself, and at school, where she is teased about her culture.